Flow-driven crystal growth of lithium phosphate in microchannels. Issue 29 (7th July 2020) - Emmanuel, Michael; Horváth, Dezső; Tóth, Ágota
Abstract : Flow-driven asymmetric growth of lithium phosphate in the presence of concentration gradients in a microchannel. Abstract : Fine tuning of the precipitation process is possible through self-organization in flow-driven systems. The reacting precursors, lithium chloride and sodium phosphate, are injected simultaneously into the microchannel where the precipitation reaction takes place in the presence of concentration gradients. The growth kinetics of individual precipitate particles is studied by monitoring the particle growth along and transverse to the flow. In the former direction, growth is constant in the stationary concentration field, while in the latter a slowing down is observed. The temporal scaling reveals a significant advective contribution in the transverse orientation as well. Polycrystalline aggregates of orthorhombic lithium phosphate are synthesized with size controlled by the flow.